Consumo de cocaína no Brasil e sua associação com violência Interpessoal e comportamento suicida - II Levantamento Nacional de Álcool e Drogas - Abdalla, Renata Rigacci [UNIFESP] (2018)
Introduction: This thesis analyzes the descriptive and analytical data of cocaine use in Brazil and also its associations with two forms of violence: one directed to others, denominated here as interpersonal violence, including both the victimization and perpetration behaviors (excluding domestic violence) and one self-directed, named as suicidal behavior, considering the personal history of suicidal ideation and suicide attempts. These data are based on the II Brazilian National Alcohol and Drugs Survey (BNADS). Objectives: This is the result of three studies with data from the Second National Survey of Alcohol and Drugs (BNADS II) that aims to: Study 1: estimate prevalence of cocaine and crack use (in life and in the last year) between Brazilian adults and adolescents and to analyze possible associations with risk and protection factors. Study 2: Investigate an association between cocaine use and urban violence, having alcohol consumption and the presence of depressive symptoms as mediators. Study 3: Investigate an association between substance use (alcohol, cannabis and cocaine) and suicide ideation and attempt. Method: A cross-sectional household survey based on data from the second national survey of alcohol and drugs covering information on the consumption of all psychotropic substances as well as sales, dependence, violent behaviors and suicidal behavior. The three studies used different cutouts from the original sample of 4507 participants. Multivariate analyzes used different regression model models and chemical odds ratios (ORs) adjusted for associations in the 3 studies. Model of causal pathways for the mediator no study 2. Results: Study 1: In the last year, consumption of all as cocaine forms 2.2% in the total population, excluding the elderly group. The prevalence rate of use in life and in the last year of cocaine aspirate was of 3,9% and 1,7%, respectively. The consumption of cocaine smoked in Brazil was estimated at 1.5% for experimentation and 0.8% in the last year. The dependence on cocaine was identified in 41.4% among the users of the previous year. Study 2: About 9.3% of the Brazilian population has already been the victim of at least one form of urban violence. This proportion increases to 19.7% among cocaine users and to 18.1% among alcohol use disorders (AUD). The perpetration of violence was reported in 6.1% of the sample. The use of cocaine and AUD increased by almost four times as a chance of being an aggressor. Being religious and married were protective factors both in relation to victimization and perpetration. Causal paths analysis was assessed considering cocaine use as a predictor of urban violence (victimization or perpetration) and alcohol consumption and depressive symptoms as mediators of this relation and all the paths were valid. Study 3: Suicide Ideation (SI) and Suicide Attempts (SA) were reported by 9.9% and 5.4% of the sample, respectively. This prevalence was 20.8% and 12.4% among problematic alcohol users, 31.5% and 16.5% among cannabis users and 40.0% and 20.8% among cocaine users. After adjusting for demographic characteristics, religion, tobacco use, family history of suicide and depressive disorder, both SI and SA were positively associated with alcohol, cannabis and cocaine misuse. Conclusion: Brazil has relevant rates of cocaine use, including the smoked form. Although men have a higher frequency of use, women are more vulnerable to the worst effects of cocaine, as well as younger population with precarious schooling. Although it does not establish causality, the association between substance use and violence, whether interpersonal or self-directed, is well proved. Depression is a frequently observed variable in all cases, assuming that the association between substance use, violent behavior and depression is a reciprocal and multidirectional relationship.